usage hydraulic press to separate sap from Eucheuma cottonii - Jamal Basmal (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
Function of hydraulic press in fresh handling of seaweed is to separate sap from its thallus tofasten its drying process. A device model of hydraulic press has been developed at the ResearchCenter for Marine and Fisheries Product Processing and Biotechnology with a pressure energy(force power) of 30 tons at 4 kWh. During the use of force power of 10 tons/900 cm2for 10 minutesfor 10 kg of seaweed, 20.6% of sap was obtained. Sap is known to contain 2,000 ppm of auxin,1,500 ppm of giberelin (GA3), 1,200 ppm of zeatin and 1,000 ppm of kinetine. In horticulture, ithas been applied to promote growth rate in plants and to increase the production of fruits.